PENGARUH PENGAWASAN TERHADAP SEMANGAT KERJA KARYAWAN TETAP PADA PT. AIR JERNIH DESA ALIANTAN KABUPATEN ROKAN HULU - Rahmat, Yogie (Jurnal Apresiasi Ekonomi, 2021)
Abstract: This study aims to determine the effect of supervision on the morale of permanent employees at PT. Clear Water in Aliantan Village, Rokan Hulu Regency. The number of samples in this study were 36 permanent employees. The results of this study indicate that the results of the overall validity test of the variable question items are declared valid because rcount > rtable (0.3291). The results of the simple linear regression test obtained the value of Y=7.090+0.840X. From the results of the t-test hypothesis test, the tcount value (13,715) is greater than the ttable value (2,03224) with a significant level of 0.000 <0.05, which means that supervision has a positive and significant effect on the morale of permanent employees. And from the results of the coefficient of determination test (R2) obtained a value of (0.847) which means that the influence of the independent variable (supervision) on the dependent variable (work spirit) is 84.7% while the remaining 15.3% is influenced by other variables not observed by the study.